Legal Analysis of Errors in Environmental Crime Decisions (International Journal of Cultural and Social Science, 2022)
This research is motivated by the right that we as living beings who participate in living on earth are obliged to protect and preserve the environment for a long, healthy and prosperous life. Referring to this, if we observe further, the mistakes or actions committed by humans with the capacity to damage or pollute the environment are usually more to cover up what they have done, even though it is clear that actions that are categorized as destructive must be very dangerous and risky for themselves to human beings. another life. The research method used is a normative juridical and sociological juridical research method. normative juridical law research is aimed at written documents sourced from legislation such as: the Criminal Code, Law Number 32 of 2009 concerning Environmental Protection and Management, and the Qur'an, and the Legal Dictionary. While sociological juridical see the law appears in the reality in society, see the effectiveness of the law that is currently in effect providing protection against environmental destruction. The purpose of this research is to find out and analyze the legal arrangements for the elements of error in environmental crimes. To find out and analyze the factors that cause environmental destruction. The results of this study can be used as material for further studies to contribute ideas for the development of criminal law, especially on the element of error in environmental crimes. As for the practical benefits of this research, namely for law enforcement officers in the criminal justice system, this research is expected to provide input for policy makers in the formulation and legislation related to criminal law, especially in the environmental field.